CORPORA ISSUES IN PROTOPROVERBIALS AND POSTPROVERBIALS OF YORUBA CULTURE - Ajadi, Rasaq Atanda; Oloruntoba-Oju, Taiwo (Proverbium - Yearbook, 2023)
Paroemia has been established as residual knowledge bequeathed by culture and tradition. However, the fact that society is always in a state of flux has made the exploration of corpora on postproverbials expedient. This study explores the problem of corpora in postproverbial studies. Primarily, it used the desk research method to examine methodological issues in corpora studies of postproverbials to advance a data-driven approach to the study of postproverbials. It is observed that samples of ‘postproverbials’ are too minute to be considered significantly threatening to the proto-texts; more postproverbials would emerge while the existing protoproverbials will continue to feature and maintain influence on modern culture; the emerging postproverbials corpora would not constitute a significant threat or impediment to the proto-text as is sometimes feared. The study concludes that postproverbials are ephemeral or transient phenomena; while they may exist side-by-side with the protoproverbials for a while, they often vanish while new forms are minted from time to time. However, protoproverbials are permanently etched on communal consciousness. It is recommended that to maintain the integrity of postproverbial data and validate related arguments, the data gathering process and parameters for the classification of samples should be made more empirical.